PENGARUH RESILIENSI DAN KOMITMEN TERHADAP KINERJA YANG DIMEDIASI KETERIKATAN KARYAWAN (Studi pada Karyawan Tidak Tetap CV Bumi Buana Citra Malang) - Muhammad Yussac Faried; Nasharuddin Mas; Soedjono (Bajang Institute, 2024)
The aim of this research is to obtain empirical evidence of the ability of resilience and commitment to encourage increased employee performance, both directly and through the mediation of employee engagement. This type of research is quantitative with the SEM-SmartPLS method. Data was obtained through a questionnaire distributed to 64 employees of CV Bumi Buana Citra Malang. Empirical evidence shows that the two independent variables, namely resilience and commitment, are both able to encourage increased employee performance. The mediating role of employee engagement is also strong, both in terms of the influence of resilience on employee performance, as well as the influence of commitment on employee performance at CV Bumi Buana Citra Malang.